Proposed Strategy for Maintaining a Small-Family-Business Enterprise in A Competitive Property Market - Aliya Mayendra (CV. Publikasi Indonesia, 2024)
The property sector's increasing complexity, driven by rapid urbanization, evolving consumer preferences, and stringent regulations, necessitates a robust strategic framework. This research aims to identify internal and external challenges faced by Allure Realty Group, develop a strategic model to address these challenges and implement actions to enhance operational efficiency, customer engagement, and market expansion. A systematic methodology combining qualitative and quantitative approaches guides this study. The research process includes problem identification, theoretical framework development, data collection through surveys and interviews, and thorough analysis using statistical and content analysis techniques. Internal analysis employs the Marketing Mix 7P, VRIO Framework, and STP Analysis, while external analysis utilizes the Marketing Mix 7P, PESTLE Analysis, Porter's Five Forces, Competitor Analysis, and Customer Analysis. Anticipated outcomes include an improved operational framework, heightened customer satisfaction, and increased market share, fostering business growth. Upon completion, this research is expected to significantly contribute to business management, particularly strategies for small family businesses in dynamic markets. The findings aim to provide a blueprint for integrating traditional business values with modern strategic management practices, offering a valuable resource for academic scholars and practitioners to understand and navigate the complexities of the property market.